2015
DOI: 10.1007/s00421-015-3196-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform recruitment along human rectus femoris muscle during transcutaneous electrical nerve stimulation

Abstract: Our results suggest that motor unit properties in proximal and other regions are not uniform within the RF muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…In support of this view, Hodson-Tole et al (48) and Vieira et al (67) showed the preferential recruitment of proximal regions of the MG muscle during electrically elicited contraction. Using a similar methodology, we also confirmed that electrical nerve stimulation can preferentially recruit motor units located in proximal regions of the RF muscle (59). According to the consideration that larger motor nerves, innervating muscle fibers that contribute to higher contraction forces, are preferentially activated by nerve stimulation (68,69), the regions that are selectively activated by electrically elicited contraction in these previous studies may be composed of muscle fibers that contribute to higher contraction forces.…”
Section: Physiological Basis and Roles Underpinning The Region-specif...supporting
confidence: 76%
See 1 more Smart Citation
“…In support of this view, Hodson-Tole et al (48) and Vieira et al (67) showed the preferential recruitment of proximal regions of the MG muscle during electrically elicited contraction. Using a similar methodology, we also confirmed that electrical nerve stimulation can preferentially recruit motor units located in proximal regions of the RF muscle (59). According to the consideration that larger motor nerves, innervating muscle fibers that contribute to higher contraction forces, are preferentially activated by nerve stimulation (68,69), the regions that are selectively activated by electrically elicited contraction in these previous studies may be composed of muscle fibers that contribute to higher contraction forces.…”
Section: Physiological Basis and Roles Underpinning The Region-specif...supporting
confidence: 76%
“…In agreement with this view, we found that patellar tendon reflex responses of proximal RF different when the flexion moment about the knee joint was varied (58). In addition, we showed that cutaneous electrical stimulation at femoral and posterior tibial nerves elicits region-specific action potentials along the RF and MG muscles (48,59). These findings suggest that motor units with territories located in proximal and distal regions of the RF and MG muscles may be independently controlled, presumably according to their functional roles at the spinal cord level or upstream of motor neuron.…”
Section: Introductionmentioning
confidence: 99%